Gypsum, Saline County - Scneller, Brett (Kansas State University, The Chapman Center for Rural Studies, 2012)
This paper is a study of the closure of Gypsum Rural High school in Gypsum, Saline County, Kansas, and how its closure affected the community surrounding and supporting it. The study includes census data, historical newspaper articles, and web articles as well as a photograph of the school.
Brett Scneller, “Gypsum, Saline County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/86.
Keywords: Assaria; Gypsum; Gypsum Rural High School; Kipp; Saline County; Southeast Saline High School